C.05 Direct visualization of the human zona incerta region using ultra-high field imaging: implications for stereotactic neurosurgery. (5th June 2019) - Lau, JC; Peters, TM; Xiao, Y; Gilmore, G; MacDougall, KW; Currie, C; Khan, AR; Parrent, AG
Abstract : Background: The zona incerta (ZI) is a small structure in the deep brain first identified by Auguste Forel for which robust in vivo visualization has remained elusive. The increased inherent signal from ultra-high field (7-Tesla or greater; 7T) magnetic resonance imaging (MRI) presents an opportunity to see structures not previously visible. In this study, we investigated the possibility of using quantitative T1 mapping at 7T to visualize the ZI region.Methods: We recruited healthy participants (N=32) and patients being considered for deep brain stimulation therapy as part of a prospective imaging study at 7T. Computational methods were used to process and fuse images to produce a high-resolution group average from which ZI anatomy could be delineated.Results: We pooled 7T data using image fusion methods and found that the contrast from quantitative T1 mapping was strikingly similar to classic histological staining, permitting facile identification of the ZI and nearby structures in reference to conventional stereotactic atlases.Conclusions: Using computational neuroimaging techniques, we demonstrate for the first time that the ZI is visible in vivo . Furthermore, we determined that this nuclear region can be decoupled from surrounding fibre pathways. This work paves the way for more accurate patient-specific optimization of deep brain targets for neuromodulation.